A comparison of methods for estimating spectral power densities of EEG signals - Andel, J; Cipra, T; Tomásek, L; Formánek, J; Kubát, J; Dvorák, J (Homeostasis in health and disease, 1991)
The paper suggests an objective method for the choice of a suitable estimate of the spectral power density in the context of the analysis of biosignals. The method is based on the principle evaluating the degree of prewhitening (i.e. elimination of autocorrelation): this prewhitening is achieved just by means of filters exploiting the compared spectral estimates. The method is demonstrated by a practical example estimating the spectral power density of EEG signals.
Keywords: algoritmy; elektroencefalografie; Electroencephalography; Humans; Algorithms; interpretace statistických dat; Data Interpretation, Statistical; lidé